2022
DOI: 10.1126/sciadv.abo5578
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA mimi scaffolds neuronal granules to maintain nervous system maturity

Abstract: RNA binding proteins and messenger RNAs (mRNAs) assemble into ribonucleoprotein granules that regulate mRNA trafficking, local translation, and turnover. The dysregulation of RNA-protein condensation disturbs synaptic plasticity and neuron survival and has been widely associated with human neurological disease. Neuronal granules are thought to condense around particular proteins that dictate the identity and composition of each granule type. Here, we show in Drosophila that a previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Many neuronal mRNAs are packaged into mRNP granules for their transport into distal processes where they are locally translated (Bauer et al 2023; Grzejda et al 2022; Knowles et al 1996; Holt et al 2019). The mRNAs in these particles are densely packaged with proteins and have been observed to have low accessibility to FISH probes (Bauer et al 2023; Fritzsche et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Many neuronal mRNAs are packaged into mRNP granules for their transport into distal processes where they are locally translated (Bauer et al 2023; Grzejda et al 2022; Knowles et al 1996; Holt et al 2019). The mRNAs in these particles are densely packaged with proteins and have been observed to have low accessibility to FISH probes (Bauer et al 2023; Fritzsche et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…115 Acting as miRNA sponges or competing endogenous RNAs (ceRNAs), decoys, and scaffolds, lncRNAs are responsible for the regulation of gene expression and are involved in various physiological and pathological processes. [116][117][118] Delivered by exosomes, lncRNAs are transported to diverse cells and tissues. However, few studies have focused on the relationship between adipose exosomal lncRNAs and metabolic diseases (Table 5).…”
Section: Roles Of Adipose Exosomal Long Noncoding Rnas In Metabolic D...mentioning
confidence: 99%
“…LncRNAs are a family of non‐protein‐coding RNA transcripts longer than 200 nucleotides with low stability and low abundance 115 . Acting as miRNA sponges or competing endogenous RNAs (ceRNAs), decoys, and scaffolds, lncRNAs are responsible for the regulation of gene expression and are involved in various physiological and pathological processes 116–118 . Delivered by exosomes, lncRNAs are transported to diverse cells and tissues.…”
Section: Roles Of Adipose Exosomal Long Noncoding Rnas In Metabolic D...mentioning
confidence: 99%
“…While some may be a product of transcriptional noise (Brosius and Raabe, 2016;Xu et al, 2023), thousands of lncRNAs (including many "antisense" RNAs) have been shown to have biological effects when their sequence or expression is perturbed and, while most have not been investigated, indices of their functionality include differential expression, subcellular localization, promoter and splice site conservation, multiexonic structure and extensive alternative splicing (Mattick and Amaral, 2022;Mattick et al, 2023), the latter shown to affect enhancer activity (Tan and Marques, 2022). Like lncRNAs generally (although there are exceptions, such as lncRNAs associated with more generic subnuclear domains such as nucleoli, paraspeckles and neuronal granules Yamazaki and Hirose, 2021;Grzejda et al, 2022)), elncRNAs are expressed at relatively low levels and exhibit only modest conservation across species (Deveson et al, 2017;Sartorelli and Lauberth, 2020;Mattick et al, 2023), features consistent with cell-and lineage-specific regulatory functions.…”
Section: Transcription From Enhancersmentioning
confidence: 99%